Effect of Short-Interval Training on the Agility of Elementary School Students in Physical Education Classes - Irfan Fauzan Syamsudin; Anggia Suci Pratiwi; Sunanih (BASICA, 2026)
This study aimed to examine the effect of short-interval-based physical activity on students’ agility in Physical Education, Sports, and Health (PJOK) at the elementary school level. Short-interval training is a structured exercise model performed at moderate to high intensity with brief recovery periods, designed to develop physical fitness components, particularly agility. The research employed a quasi-experimental pretest–posttest control group design. The participants were 54 students from SDN Sambongpari, divided into an experimental group (n = 27) and a control group (n = 27). The intervention was conducted over six instructional sessions. The experimental group received PJOK instruction integrated with short-interval training, while the control group followed conventional Intruction. Agility was measured using the standardized T-Test and analyzed through descriptive statistics, the Wilcoxon Signed-Rank Test, and the Mann–Whitney U test at a 0.05 significance level. The results showed a significant improvement in the experimental group (p = 0.014 < 0.05), whereas the control group showed no significant change (p = 0.317 > 0.05). The Mann–Whitney U test also revealed a significant difference between the experimental and control groups (p = 0.013), with Z = −2.492 and an effect size of r = 0.34, indicating a moderate between-group effect. The experimental group demonstrated an average improvement of 7.89% in agility performance, while the control group showed a decline of 1.30%. These findings indicate that short-interval training delivered over six sessions is effective for developing agility in elementary students. PJOK teachers can implement short-interval activities to promote practical learning outcomes in school settings.